From La Boca to La Stocka (Alternautas, 2024)
In this short reflection piece, we hear from Neil West, who recently co-organised a project between artists in La Boca in Buenos Aires, Argentina, and Stockport, near Manchester in the UK. The piece brings together anecdotes and personal photographs as documentation of collective, cultural political practice.